Emotional Intelligence Features Of Students With Different Levels Of Emotional Burnout - Koltunovych, Tetiana; Polishchuk, Oksana (Future Academy www.FutureAcademy.org.UK, 2019)
Our main objective was to determine the possibility of using emotional intelligence as a potential resource in overcoming emotional burnout among students. The article confirms the assumption about the existence of correlation and casual interconnection between emotional burnout and emotional intelligence. It has been empirically proved that emotional burnout (p≤0.05) and depersonalization (p≤0.01) have a stronger effect on emotional intelligence; and it’s the level of emotional intelligence that determines emotional exhaustion (p≤0.01) and reduction of personality achievements (p≤0.05). Persons’ ability to understand their own emotions (p≤0.01), intrapersonal emotional intelligence (p≤0.01), emotional control (p≤0.05) effect emotional burnout, which in its turn is influencing expression control (p≤0.01). In particular, students with a high level of burnout are characterized by worse level of understanding their own emotions (p=0.003), while it’s a more situational relation in cases with students with average burnout. The relation between the ability to manage one’s own and others’ emotions in this group is weaker (p=0.006) than in a sample of students with a low level of emotional burnout; as well as their relation between intrapersonal emotional intelligence (p=0.006) and control of expression (р=0.044), compared to students with average and low levels of burnout. The obtained data contribute to the study of the burnout phenomenon and provide an opportunity to determine further directions of its prevention and correction in students by means of emotional intelligence development.
Keywords: Emotional intelligence, understanding emotions, managing emotions, control of expression, emotional burnout